2010
DOI: 10.1128/cvi.00160-10
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Assay Detection of Immunoglobulin G Antibodies That Recognize Giardia intestinalis and Cryptosporidium parvum Antigens

Abstract: Giardiasis and cryptosporidiosis are common enteric parasitic diseases that have similar routes of transmission. In this work, we have identified epitopes within the Giardia variant-specific surface protein (VSP) sequences that are recognized by IgG antibodies from 13 of 14 (93%) sera from patients with stool-confirmed giardiasis. The conserved epitopes are shared among VSPs from both of the assemblages that commonly infect humans, and they are likely to be structural, as both sodium dodecyl sulfate treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 86 publications
(97 reference statements)
1
68
2
Order By: Relevance
“…A number of previous studies have reported serum antibody responses to p23 [30][31][32][33][34][35][36] in immunocompetent and immunocompromised hosts. However, most studies were serosurveys to estimate prevalence and investigate outbreaks 32,33,[56][57][58][59][60] or to demonstrate the utility of p23 as an antigen for ELISAs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of previous studies have reported serum antibody responses to p23 [30][31][32][33][34][35][36] in immunocompetent and immunocompromised hosts. However, most studies were serosurveys to estimate prevalence and investigate outbreaks 32,33,[56][57][58][59][60] or to demonstrate the utility of p23 as an antigen for ELISAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies were serosurveys to estimate prevalence and investigate outbreaks 32,33,[56][57][58][59][60] or to demonstrate the utility of p23 as an antigen for ELISAs. 30,35 Priest and others investigated serum antibody responses to a 27-kDa antigen (same as p23) in a birth cohort of children in Peru by using the same recombinant C. parvum protein we used as antigen for the ELISA. As in our study, most children in their study were infected with C. hominis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations